Transformasi Kehidupan Melalui Perubahan Kebiasaan Perspektif Daniel 1 Konteks Keberagaman Kultural - Rakhmad Widodo Dwi Sasono; Samuel Herman (Jurnal Teologi Berita Hidup, 2024)
This article explores life transformation through habit transformation, focusing on Daniel's perspective in facing cultural diversity. By examining the impact of sin on humanity and the coercion faced by displaced nations, Daniel serves as an illustration that negative experiences can be the best teachers for behavioral change. The article underscores that changing habits requires effective efforts, especially within the framework of cultural diversity. Consistency, patience, and awareness of the adverse consequences of habits are key to successfully shaping a resilient character. By presenting novel ideas on life transformation, the article provides a unique perspective on Daniel's journey in confronting cultural diversity.